ASSESSMENT OF PASSENGER COMFORT ON THE FAST FERRY OPERATING IN THE STRAIT OF MALACCA - Jamal; Sulisetyono, Aries; Aryawan, Wasis Dwi (Journal of Applied Engineering Science, 2023)
The ship operator needs passenger feedback on the comfort of inter-island speed ferries as information on improving passenger comfort services. This paper analyzes the comfort of passengers on fast passenger ferries operating in the Malacca Straits directly. The survey focuses on directly assessing the level of passenger comfort and evaluating the leading causes of passenger discontentment. The strategy adopted is the dissemination of a questionnaire to onboard passengers, with a response rate of around 30 out of a minimum of 24 referring to the SLOVIN formula. The comfort score in the questionnaire is divided into five points, namely: uncomfortable or queasy, dizzy and slightly queasy, dizzy, slightly dizzy, and comfortable. The measured data were validated using Analysis of Variance (ANOVA) and the Dunnett Simultaneous Tests for Differences in Means, which gave a P-value of 0.000 and a degree of confidence of 98.97%. The findings of the study indicated that respondents, on average, rated this ship as slightly uncomfortable to comfortable, giving it a comfort rating of 4.10 out of a possible 5. Moreover, three aspects, namely the ship’s motion, the accommodation facilities, and the ship’s vibration, significantly contribute to discomfort, as indicated by ratings of 3.8, 4.2, and 4.2, respectively, out of 5 (comfortable), indicating the severity of the effect. Furthermore, by knowing that the main source of passenger discomfort is ship motion, it can be input for ship operators in managing the comfort of ship passengers.